Antibacterial activity of aloe vera in inhibiting the growth of methicillin-resistant Staphylococcus aureus - Ni Putu Ratih Permata Dewi Arya; Anak Agung Ayu Lila Paramasatiari; Ni Wayan Widhidewi; Marta Setiabudy (Journal of Clinical Microbiology and Infectious Diseases, 2026)
Introduction: Antibiotic resistance is an increasing global health problem, particularly associated with Methicillin-Resistant Staphylococcus aureus (MRSA), which shows resistance to β-lactam antibiotics and can cause severe infections. This condition has encouraged the exploration of alternative antibacterial agents derived from natural sources. Aloe vera contains various bioactive compounds, such as saponins, flavonoids, tannins, and phenolic compounds, which potentially exhibit antibacterial activity. This study aimed to determine the effectiveness of Aloe vera extract in inhibiting the growth of MRSA. Methods: This experimental laboratory study employed a posttest-only control group design using the disk diffusion method on Mueller–Hinton agar. Aloe vera extract was tested at concentrations of 15μg/mL, 20μg/mL, 25μg/mL, and 50μg/mL. Vancomycin and 0.9% NaCl were used as positive and negative controls, respectively. Antibacterial activity was evaluated by measuring the diameter of inhibition zones. Data were analyzed descriptively. Result: The findings indicated that all concentrations of Aloe vera extract failed to produce inhibition zones against MRSA, with inhibition diameters of 0.00 mm. The positive control showed strong antibacterial activity, whereas the negative control exhibited no inhibitory effect. Conclusion: Aloe vera extract at concentrations of 15%, 20%, 25%, and 50% was not effective in inhibiting the growth of Methicillin-Resistant Staphylococcus aureus (MRSA) under in vitro conditions